Programming Excel with VBA and .NET - Saunders, Steve (O'Reilly, 2006)
Why program Excel? For solving complex calculations and presenting results, Excel is amazingly complete with every imaginable feature already in place. But programming Excel isn't about adding new features as much as it's about combining existing features to solve particular problems. With a few modifications, you can transform Excel into a task-specific piece of software that will quickly and precisely serve your needs. In other words, Excel is an ideal platform for probably millions of small spreadsheet-based software solutions. The best part is, you can program Excel with no additional to.